Effects of bioactive constituents in functional cocoa products on cardiovascular health in humans. (1st May 2015) - Sarriá, Beatriz; Martínez-López, Sara; Sierra-Cinos, José Luis; Garcia-Diz, Luis; Goya, Luis; Mateos, Raquel; Bravo, Laura
Highlights: Regularly consuming moderate amounts of functional cocoa products induces CV benefits. Flavanols in functional cocoa products are responsible for the HDL-cholesterol increase. Insoluble-dietary-fibre in fibre rich cocoa is responsible for hypoglycemic effects. Theobromine may contribute to the hypoglycemic effects of cocoa. Abstract: Cocoa manufacturers are producing novel products increasing polyphenols, methylxanthines or dietary fibre to improve purported health benefits. We attempt to explain the contribution of cocoa bioactive compounds to cardiovascular effects observed in previous studies, placing particular emphasis on methylxanthines. We focused on a soluble cocoa product rich in dietary fibre (DFCP) and a product rich in polyphenols (PPCP). Effects of regularly consuming DFCP (providing daily 10.17 g, 43.8 mg and 168.6 mg of total-dietary-fibre, flavanols and methylxanthines, respectively) as well as PPCP (providing daily 3.74 g, 45.3 mg and 109.8 mg of total-dietary-fibre, flavanols and methylxanthines, respectively) on cardiovascular health were assessed in two controlled, cross-over studies in free-living normocholesterolemic and moderately hypercholesterolemic subjects. Both products increased HDL-cholesterol concentrations, whereas only DFCP decreased glucose and IL-1β levels in all subjects. Flavanols appeared to be responsible for the increase in HDL-cholesterol, whereas insoluble-dietary-fibre and theobromine in DFCP were associated with the hypoglycemic and anti-inflammatory effects observed.